Formação continuada para educadores da educação infantil - Fink, Jéssica Hensel (My University, 2022)
The present work addresses the theme Continuing Education for Early Childhood Education Educators, in order to investigate its role in the professional training and qualification of pedagogical practices at this level of education. Therefore, this investigation sought to answer the problem "How can continuing education contribute to the professional development of educators who work in Early Childhood Education for the mobilization of significant pedagogical practices?" The described investigation, of an applied nature, qualitative in terms of approach, exploratory in relation to its objectives, in the field modality, was developed through the case study methodology (GIL, 2008), with application of semi-structured interviews to educators who work in the area of Early Childhood Education, being them teachers, monitors and educational assistants. The collected data were analyzed using the discursive textual analysis technique (MORAES, 2003) and based on theoretical contributions, among which I highlight Teodoro (2013), Moreno (2007), Vygotsky (1998), Piaget (2008), Kramer (2005 ), Nóvoa (1995), among others. Said discursive textual analysis enabled the identification of concepts and blocks of studies that are fundamental for the construction of knowledge to respond to the research problem, namely: Early Childhood Education and its childhood, Training to work in Early Childhood Education: initial and continuing, Continuing Education and Pedagogical Practice in Early Childhood Education. The research carried out enabled a broad understanding of the topic in focus. As a result of the research, it is possible to affirm that Continuing Education is extremely necessary and enables important contributions to the education of investigated educators. This training contributes so that they can constantly qualify, improving their professional career more and more, improving their pedagogical practice and promoting quality education in the first stage of Basic Education. It also promotes reflection on practice, keeps educators updated and committed to learning and teaching, with meaningful strategies, making them feel part of a context that forms citizens, subjects capable of acting ethically in the world in which they live. [resumo fornecido pelo autor]
O presente trabalho aborda o tema "Formação Continuada para Educadores da Educação Infantil", no sentido de investigar seu papel na formação profissional e qualificação das práticas pedagógicas neste nível de ensino. Para tanto, a referida investigação buscou resposta ao problema "Como a formação continuada pode contribuir no desenvolvimento profissional dos educadores que atuam na Educação Infantil para a mobilização de práticas pedagógicas significativas?" A investigação descrita, de natureza aplicada, qualitativa quanto à abordagem, exploratória em relação aos seus objetivos, na modalidade de campo, foi desenvolvida através da metodologia de estudo de caso (GIL, 2008), com aplicação de entrevistas semiestruturadas a educadores que atuam na área da Educação Infantil sendo eles professores, monitores e auxiliares de educação. Os dados coletados foram analisados por meio da técnica de análise textual discursiva (MORAES, 2003) e fundamentados em aportes teóricos entre os quais destaco Teodoro (2013), Moreno (2007), Vygotsky (1998), Piaget (2008), Kramer (2005), Nóvoa (1995), entre outros. A referida análise textual discursiva possibilitou a identificação de conceitos e blocos de estudos fundamentais para a construção de conhecimentos para dar respostas ao problema de investigação, a saber: a Educação Infantil e sua infância, A formação para atuação na Educação Infantil: inicial e continuada, A Formação Continuada e a prática pedagógica na Educação Infantil. A pesquisa realizada possibilitou uma ampla compreensão acerca da temática em foco. Como resultado da pesquisa é possível afirmar que a Formação Continuada é de extrema necessidade e possibilita importantes contribuições para a formação dos educadores investigados. A referida formação contribui para que os mesmos possam se qualificar constantemente, aperfeiçoando cada vez mais sua carreira profissional, aprimorando sua prática pedagógica e promovendo uma educação de qualidade na primeira etapa da Educação Básica. Ainda, promove a reflexão sobre a prática, mantém os educadores atualizados e comprometidos a aprender e ensinar, com estratégias significativas, fazendo com que se sintam parte de um contexto que forma cidadãos, sujeitos capazes de agirem de forma ética no mundo em que vivem. [resumo fornecido pelo autor]
Keywords: Educação; Educadores; Professores - Formação; Professores de educação infantil; Educação permanente; Aprendizagem